Association between telomere length and survival in patients with idiopathic pulmonary fibrosis. Issue 6 (14th June 2015) - Dai, Jinghong; Cai, Hourong; Li, Hui; Zhuang, Yi; Min, Haiyan; Wen, Yanting; Yang, Jie; Gao, Qian; Shi, Yi; Yi, Long
Abstract Background and objective Short telomere is a crucial risk factor for idiopathic pulmonary fibrosis (IPF). However, little is known about the association between baseline telomere length and survival in IPF. We aimed to determine whether telomere length is associated with survival of IPF. Methods Leukocyte telomere lengths were measured by quantitative polymerase chain reaction in IPF patients at the time of the initial enrolment assessment in Nanjing Drum Tower Hospital Affiliated to Medical School of Nanjing University. The primary endpoint was the survival of the IPF patients since their initial enrolment assessment. Results Ninety‐four IPF patients were enrolled between 1 January 2012 and 30 June 2014. The mean age‐adjusted telomere length of IPF patients (0.85 ± 0.60) was significantly shorter than age‐matched controls (1.15 ± 0.60, P = 0.001). During the follow‐up period, 43 IPF patients died. The mean age‐adjusted telomere length of the non‐survivors (0.61 ± 0.53) was significantly shorter than that of the survivors (1.03 ± 0.59, P = 0.005). The association between telomere length (hazard ratio (HR) 0.470 (95% confidence interval (CI): 0.25–0. 89); P = 0·019) and survival in patients with IPF was independent of age, sex, forced vital capacity or diffusing capacity of carbon monoxide. After excluding the six patients with telomerase gene mutations, telomere length (HR 0.46 (95% CI: 0.24–0.88); P = 0·018) remained an independent predictor of survival time in patients with IPF. Conclusions Short telomere length is independently associated with worse survival in IPF. Future research should focus on the molecular mechanism underlying the shortening of telomere length in IPF.